1999
DOI: 10.1136/bjo.83.9.1069
|View full text |Cite
|
Sign up to set email alerts
|

alpha /beta - and gamma /delta TCR+ lymphocyte infiltration in necrotising choroidal melanomas

Abstract: T cells can play a central role in the local immune response to cancer with tumour specific T lymphocyte reactivity provided by the TCR variable genes V /V chain heterodimer or the V or V chains. The identification and functional characterisation of MHC class I restricted antigen specific TCR expressing tumour infiltrating lymphocytes (TIL) has been the subject of intense research in the recent years, since tumour reactivity by these genes may provide novel applications for immunotherapy including the redirect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 22 publications
1
28
0
Order By: Relevance
“…[5][6][7] Vd1 1 cd TILs are present in melanoma, and the infiltration of these cells into necrotizing melanoma correlates with survival. 17 Orthotopic xenografts of the HT29 colon cancer cells in mice infused with human TCRVd2 2 cd T lymphocytes also carried cd TILs that impaired tumor development. 18 In prostate and breast tumors, however, Vd1 1 cd TILs are rather immunosuppressive for dendritic cells and T cells 19 and favor the growth of the tumor through IL-10 release.…”
Section: Rationale For Harnessing CD Cells In Cancer Immunotherapymentioning
confidence: 99%
“…[5][6][7] Vd1 1 cd TILs are present in melanoma, and the infiltration of these cells into necrotizing melanoma correlates with survival. 17 Orthotopic xenografts of the HT29 colon cancer cells in mice infused with human TCRVd2 2 cd T lymphocytes also carried cd TILs that impaired tumor development. 18 In prostate and breast tumors, however, Vd1 1 cd TILs are rather immunosuppressive for dendritic cells and T cells 19 and favor the growth of the tumor through IL-10 release.…”
Section: Rationale For Harnessing CD Cells In Cancer Immunotherapymentioning
confidence: 99%
“…In a pilot study, we recently identified the frequency of circulating Vδ1+ γδ T-cells as a negative prognostic marker candidate for advanced melanoma patients (31). In contrast, tumor-infiltrating Vδ1+ cells were reported to have a positive impact on survival of melanoma patients (32). Vδ2+ cells were decreased in the peripheral blood and had impaired functionality in melanoma compared to healthy controls in a study by Petrini et al (29).…”
Section: Introductionmentioning
confidence: 99%
“…gd TILs isolated in various types of cancer, including colorectal, breast, prostate, ovarian and RCC [17,24,25], recognize and kill both the autologous tumor and a broad range of related tumors, presumably via the recognition of shared stress-related ligands, but do not kill nontransformed cells [17,25]. The infiltration of Vg1 and Vd1 gd T cells into necrotizing melanomas (NMMs) significantly correlates with increased survival [26], whereas intratumoral gd T cell infiltration in RCC tumors does not [27]. These studies suggest that gd T cell infiltration might be beneficial; however, the immunoregulatory properties of gd T cells should not be ignored [28].…”
mentioning
confidence: 98%